2010
DOI: 10.1203/pdr.0b013e3181d4ecda
|View full text |Cite
|
Sign up to set email alerts
|

Decreased aEEG Continuity and Baseline Variability in the First 48 Hours of Life Associated With Poor Short-Term Outcome in Neonates Born Before 29 Weeks Gestation

Abstract: Amplitude-integrated electroencephalography (aEEG) provides us with a method of assessing brain activity in critically ill neonates. In extremely premature neonates, the aEEG trace is predominantly discontinuous, making it difficult to distinguish between a "normal" and "abnormal" trace. We measured aEEG activity in the first 48 h of life in neonates born before 29-wk gestation and used both visual and quantitative analysis of the aEEG data to assess differences in neonates with poor short-term outcome [death … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 32 publications
(45 reference statements)
2
48
0
1
Order By: Relevance
“…Biomarkers measured at or soon after birth may be useful in diagnosing and predicting complications and future outcome. Several studies have evaluated whether, and to what extent, amplitude-integrated electroencephalogram (aEEG)-derived parameters can be used for the identification of neurological dysfunction and prediction of outcome in preterm infants (1)(2)(3)(4)(5)(6)(7). The increasing adoption of the aEEG method in the neonatal intensive care unit is reflected by the growing number of studies published during the past decade, although these still do not match the knowledge that was gained in term-born infants over the same period of time (8)(9)(10).…”
mentioning
confidence: 99%
“…Biomarkers measured at or soon after birth may be useful in diagnosing and predicting complications and future outcome. Several studies have evaluated whether, and to what extent, amplitude-integrated electroencephalogram (aEEG)-derived parameters can be used for the identification of neurological dysfunction and prediction of outcome in preterm infants (1)(2)(3)(4)(5)(6)(7). The increasing adoption of the aEEG method in the neonatal intensive care unit is reflected by the growing number of studies published during the past decade, although these still do not match the knowledge that was gained in term-born infants over the same period of time (8)(9)(10).…”
mentioning
confidence: 99%
“…The main reason to select nonparametric measures such as the median and percentiles is that they are noise-proof and, thus, insensitive to outliers with extremely high amplitudes. Moreover, the amplitude of the aEEG is not normally distributed, such that nonparametric statistics are more suitable [3,5,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we managed to obtain the accurate amplitude of the aEEG margin, which largely enhanced the objectivity of data interpretation. Quantitative aEEG margins can be obtained along with graphical tracing in some new digital aEEG devices (e.g., the NicoletOne monitor [19]) or in some off-line software (e.g., Brainz Analyze Research [5]). We believe that the aEEG algorithm, including margin display and quantitative output, can be used successfully for both individual CFMs and full-scale EEG monitoring systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have demonstrated the prognostic value of aEEG in term infants with hypoxic ischemic encephalopathy in association with depression of amplitude (2)(3)(4). Other studies have demonstrated a correlation between depressed aEEG activity and intraventricular hemorrhage in preterm infants (5)(6)(7). In many of these studies, single-channel records from the P3 to P4 electrodes were selected on aEEG.…”
mentioning
confidence: 99%